REKONSILIASI ILMU DAN AGAMA PERSPEKTIF NURCHOLISH MADJID DALAM EPISTEMOLOGI ISLAM - Junaidi; Edy Musoffa; Faiz , Fahruddin; Aryani, Sekar Ayu (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
This research discusses Nurcholish Madjid's thoughts on science and religion from the perspective of Islamic epistemology. It is a relatively difficult endeavor because one's thoughts often reflect multiple prototypes. The type of research used is a philosophical-historical hermeneutic analysis approach. In this context, the three methods are used to explore concepts related to the reconciliation of science and religion in Islamic epistemology. The data in this research were obtained through a literature study, which involved collecting books, papers, articles, and journals relevant to the research topic that reflect the understanding of the polarization of science and religion, thereby enriching research perspectives. This research is a qualitative literature review with a philosophical approach using critical analysis and historical hermeneutic methods. The research findings obtained are that Nurcholish Madjid has an ontological basis in the form of belief in the oneness of God as a basis for the development of science and religion in the Islamic world. Regarding the field of epistemology, Nurcholish Madjid has thoughts mainly related to the issue of the function of reason in science. The solution offered to the crisis in the relationship between science and religion for Nurcholish Madjid is simply to include ethical-aesthetic elements in it. Finally, for Nurcholish Madjid, science and religion are about high reality. In scientific studies, religion is a system of symbols. So there is a universal idea of science and religion, which is then translated through concrete events so that it enters the human mind. That's why the word of God is called a verse. In the language of the Quran, it is called a religion of justice and prosperity, even though humans generally do not know it.